Severe hypersensitivity reaction with erythromycin ethylsuccinate: A case report - Inder, Deep; Kumar, Pawan (Indian Journal of Case Reports, 2019)
Erythromycin is considered to be one of the safest antimicrobials exhibiting good activity against Gram-positive aerobes and some Gram-negative aerobes but rare cases of hypersensitivity reactions to erythromycin alone or with its base (esteolate or ethylsuccinate) can occur. Here, we report the case of severe hypersensitivity reaction in a female patient with upper respiratory tract infection and underwent treatment with erythromycin ethylsuccinate (400mg TDS). Twenty-four hours after the initiation of therapy with erythromycin ethylsuccinate, the patient developed severe rash starting from the nape of the neck spreading throughout the body with generalized pruritus and mild icterus. Marked improvement was noticed within 2 days after cessation of erythromycin ethylsuccinate. Physicians must be aware of the adverse effects of erythromycin ethylsuccinate before prescribing the drug.